(untitled) (Asian Journal of Agriculture, 2018)
Abstract. Mulyono, Maas A, Purwanto BH, Sudira P. 2018. Short Communication: Volcanic ash utilization as planting medium of curly lettuce with charcoal husk and urban waste compost as soil amendment. Asian J Agric 2: 39-43. During a volcanic eruption, volcanic ash spreads over an extensive area and can cause environmental disturbances. Because of this, volcanic ash should be disposed of far from settlements. On the other hand, volcanic ash is useful in urban areas where pot-planting is often lacking in soil medium. However, the utilization of volcanic ash as a direct planting medium has many obstacles due to its characteristics such as the acidic, nitrogen nutrients rareness, compressed and dull to water. Hence, to be ready to use, it should be improved by using soil amendment. This study used charcoal husk combined with compost as the soil amendment. The purpose of this study was to use the volcanic ash as the planting medium, by obtaining a proper dose of volcanic ash and the soil amendments for the growth and yield of curly lettuce. The experimental design applied in this study was the completely randomized design (CRD) with three replications. The first factor was the 5 levels of charcoal husk (on volcanic ash) doses, namely 0.30; 0.40; 0.50; 0.60; and 0.70. The second was the ratio between the media and the 3 levels of urban waste compost doses, namely: 3:1; 2:1 and 1:1, resulting in 5 x 3 total combinations with three replications. The plant growth and yield data results were analyzed by using the variance analysis and continued with Duncan Multiple tests (Duncan Multiple Range Test). The results showed that when used as the sole planting medium, the volcanic ash could not support the growth of lettuce plants. The evidence was shown from the same size and weight of the curly lettuce after the age of 35 days (5 g/plant). The utilization of husk and urban waste compost treatment showed significant growth rise. The combination of volcanic ash and soil amendments showed that the best effect on the growth and yield of curly lettuce was from M3K3 treatment at the dose of 25% volcanic ash, 25% charcoal husk and 50% urban waste compost (60 g/plant).